2018
DOI: 10.1182/bloodadvances.2017013730
|View full text |Cite
|
Sign up to set email alerts
|

Reduced red blood cell deformability in Plasmodium knowlesi malaria

Abstract: The simian parasite can cause severe and fatal human malaria. However, little is known about the pathogenesis of this disease. In falciparum malaria, reduced red blood cell deformability (RBC-D) contributes to microvascular obstruction and impaired organ perfusion. In infection, impaired microcirculatory flow has been observed in (rhesus macaques), unnatural hosts who develop severe and fatal disease. However, RBC-D has not been measured in human infection or in the natural host (long-tailed macaques). Using e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 41 publications
1
49
0
Order By: Relevance
“…These "storage-induced micro-spherocytes" are removed from the circulation (Roussel, 2019). A similar analysis of blood samples from three Plasmodium knowlesi-infected human subjects showed that sphericity was increased in iRBC compared with uninfected-RBC from the same patients (Barber et al, 2018). A reduction in the projected area of ring-infected RBC (P. falciparum culture in vitro) had also been observed using IFM and correlated with retention in microsphiltration (Safeukui et al, 2013).…”
Section: Imaging Flow Cytometrymentioning
confidence: 74%
See 3 more Smart Citations
“…These "storage-induced micro-spherocytes" are removed from the circulation (Roussel, 2019). A similar analysis of blood samples from three Plasmodium knowlesi-infected human subjects showed that sphericity was increased in iRBC compared with uninfected-RBC from the same patients (Barber et al, 2018). A reduction in the projected area of ring-infected RBC (P. falciparum culture in vitro) had also been observed using IFM and correlated with retention in microsphiltration (Safeukui et al, 2013).…”
Section: Imaging Flow Cytometrymentioning
confidence: 74%
“…Shear stresses of 30 Pa provide information on the RBC surface-tovolume ratio and may be a proxy for the ability of RBC to cross splenic slits (Barber et al, 2018). Reduced EI of circulating RBC, which contain a vast majority of uninfected RBC, in patients with malaria correlates with disease severity (Dondorp et al, 1999(Dondorp et al, , 2002Ishioka et al, 2016;Barber et al, 2018). A large-scale gene knockout strategy was combined with ektacytometry to determine the role of parasitic exported proteins in stiffness (Maier et al, 2008).…”
Section: Ektacytometrymentioning
confidence: 99%
See 2 more Smart Citations
“…It is associated with high parasitemia infections and causes severe malaria in adult humans at a rate similar to P. falciparum (Cox-Singh et al, 2008, Barber et al, 2013. P. knowlesi does not express adhesins on the surface of the host RBC, but does exhibit increased the host cellular rigidity (Barber et al, 2018b). Despite the lack of adhesion, splenic rupture has been observed, suggesting blockage of sinusoidal vessels (Chang et al, 2018) and an autopsy of a fatal human knowlesi malaria case revealed brain capillaries congested with infected RBCs (Menezes et al, 2012).…”
Section: Introductionmentioning
confidence: 99%